2020
DOI: 10.1155/2020/8836505
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Transverse Effective Bending Rigidity of Segmental Lining Structures

Abstract: The transverse effective rigidity ratio is a key parameter when the uniform rigidity ring model is adopted to design or numerically analyse segmental lining structures commonly used on a shield-driven tunnel. Traditionally, the transverse effective rigidity ratio η is treated as a constant, which can be evaluated through theoretical analysis and model tests. In this study, scale models were designed and tested to investigate the variation of the transverse effective rigidity ratio in the segmental linings’ fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Therefore, the effective stiffness ratio of tunnel η (η ≤ 1) is introduced to reflect the weakening effect of segment joints on the tunnel stiffness, i.e., the equivalent stiffness of the tunnel is ηEI, where EI is the bending stiffness of the homogeneous tunnel before stiffness reduction. Some studies [24][25][26][27][28] demonstrated that the value of η is related to the soil conditions, the form of the segment joints, and the manner of segment assembly. In this study, the value of η = 0.75 is adopted, referring to the above studies.…”
Section: Constitutive Model and Parametersmentioning
confidence: 99%
“…Therefore, the effective stiffness ratio of tunnel η (η ≤ 1) is introduced to reflect the weakening effect of segment joints on the tunnel stiffness, i.e., the equivalent stiffness of the tunnel is ηEI, where EI is the bending stiffness of the homogeneous tunnel before stiffness reduction. Some studies [24][25][26][27][28] demonstrated that the value of η is related to the soil conditions, the form of the segment joints, and the manner of segment assembly. In this study, the value of η = 0.75 is adopted, referring to the above studies.…”
Section: Constitutive Model and Parametersmentioning
confidence: 99%
“…e results show that the opening in the upward shield method aggravates the "transverse elliptical" deformation of the segment ring in the special section of the horizontal tunnel. Under the action of the lateral load term, the "transverse elliptical" deformation of the special segment ring can be alleviated to a certain extent.Tang et al[27] conducted a numerical simulation of segment rings.ey concluded that the horizontal convergence caused by excavation near the shield tunnel increases significantly as the value of η decreases. Both the opening obtained with the upward shield method and the reduction in the η value aggravate the "horizontal elliptical" deformation of the segment ring.…”
mentioning
confidence: 99%